2001
DOI: 10.1006/viro.2001.1075
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Diversity and Virulence in Zea mays of Maize Streak Virus Isolates

Abstract: Full genomic sequences were determined for 12 Maize streak virus (MSV) isolates obtained from Zea mays and wild grass species. These and 10 other publicly available full-length sequences were used to classify a total of 66 additional MSV isolates that had been characterized by PCR-restriction fragment length polymorphism and/or partial nucleotide sequence analysis. A description is given of the host and geographical distribution of the MSV strain and subtype groupings identified. The relationship between the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 35 publications
5
95
1
1
Order By: Relevance
“…A great emphasis has been emerged here stressed on the biological difference between the viral isolates would be classified into different strains. For example, whereas the ''A'' strain of MSV is clearly the only group of MSV variants that cause severe disease in maize [28,42], the ''A'' strain of WDV favourably infects barley, whereas the ''C'' strain preferentially infects wheat [39], our Egyptian isolate of CpCDV could be assigned as a specific strain preferentially infects squash which is essentially a non-host species of this virus. Through recombination analysis performed using RDP4, it has been observed that the Egyptian isolate although more closely related to the Syrian isolate but a considerable part of the genome found to be originated from a different isolate of BeYDV assigned in the genbank under accession no ENA|DQ458791 (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…A great emphasis has been emerged here stressed on the biological difference between the viral isolates would be classified into different strains. For example, whereas the ''A'' strain of MSV is clearly the only group of MSV variants that cause severe disease in maize [28,42], the ''A'' strain of WDV favourably infects barley, whereas the ''C'' strain preferentially infects wheat [39], our Egyptian isolate of CpCDV could be assigned as a specific strain preferentially infects squash which is essentially a non-host species of this virus. Through recombination analysis performed using RDP4, it has been observed that the Egyptian isolate although more closely related to the Syrian isolate but a considerable part of the genome found to be originated from a different isolate of BeYDV assigned in the genbank under accession no ENA|DQ458791 (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…We considered it possible that these recombination signals would complicate subsequent genetic distance and phylogenetic analyses aimed at relating the USV sequences to the other AfSV species. We therefore identified tracts of sequence that had a potentially recombinant origin using the RDP [12,20,24], we found no convincing evidence that any of the USV sequences were either inter-or intra-species recombinants (data not shown).Following (Fig. 1).…”
mentioning
confidence: 92%
“…Whereas members of AfSV species such as MSV and PanSV have been detected throughout the continent [4,12], [24], others such as SSEV (and now USV) have only ever been detected in individual countries. While these distribution differences may reflect sampling bias, it may also indicate that there are variable geographical and/ or ecological barriers that different AfSV species experience during their movement around the continent.…”
mentioning
confidence: 99%
“…Eleven strains of MSV have been identified and are designated MSV-A to MSV-K. MSV-A strain has been identified to be the most virulent and can cause significant MSVD while others attack cereals such as barley, wheat, oats, rye and millet but not maize (Martin et al, 2001;Shepherd et al, 2010). Oppong et al (2015) reported that MSV-A1 variant was predominant in the transition and forest zones of Ghana, and it exhibits an increased level of pathogenicity than the other MSV-A variants which are MSV-A2, MSV-A3, MSV-A4 and MSV-A6 (Martin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Oppong et al (2015) reported that MSV-A1 variant was predominant in the transition and forest zones of Ghana, and it exhibits an increased level of pathogenicity than the other MSV-A variants which are MSV-A2, MSV-A3, MSV-A4 and MSV-A6 (Martin et al, 2001). The incidence and severity of MSVD can be reduced by chemical control of leafhoppers and cultural practices such as crop rotation, irrigation, inter-cropping, application of appropriate fertilizer rate and plant density manipulation but the most economically sustainable option is provided by using disease resistant varieties (Martin and Shepherd, 2009).…”
Section: Introductionmentioning
confidence: 99%